(untitled) (Modern education and development, 2025)
The article discusses the importance of the element iron in plant and human life, the reduction in the content of vitamins, macro- and microelements during the processing of grain products, and the use of biofortification to prevent these processes.В статье рассматривается значение элемента железа в жизни растений и человека, снижение содержания витаминов, макро- и микроэлементов при переработке зерновых продуктов, а также применение биофортификации для предотвращения этих процессов.